Relationship between Gastroesophageal Reflux Disease Questionnaire (GERD-Q) Score and Reflux Oesophagitis in Gastroesophageal Reflux Disease (GERD) Suspected Patients in Bandung - Dosmer Oloan Simarmata; Yudi Wahyudi; Muhammad Begawan Bestari; Rudi Supriadi (The Indonesian Society for Digestive Endoscopy, 2019)
Background: Gastroesophageal reflux disease is a disease with heterogen symptoms, with no gold standard available to diagnose this condition. Questionnaire is a diagnostic tool that may enable an objective symptom assessment. GERD-Q questionnaire consist of 6 components of questions, formed from 4 various components of reflux symptoms (positive predictors of GERD) and 2 as negative predictors of GERD. This study aimed to observe the relationship between GERD-Q score and reflux oesophagitis in GERD suspected patients.Method: This study was an analytic cross-sectional study, conducted in March to July 2019. Study participants were patients visiting the Endoscopy Unit in Hasan Sadikin Hospital, Cibabat District General Hospital, and Al Islam General Hospital, who were then evaluated using GERD-Q and later underwent endoscopy examination. The severity of reflux oesophagitis observed through endoscopy was evaluated using the Los Angeles classification. Endoscopy readings was performed by one experienced doctor.Results: Thirty-six patients were examined; 17 (47.2%) patients suffered from reflux oesophagitis, including 13 cases with grade A (76.5%) and 4 cases with grade B (23.5%). There were no cases with grade C or grade D was found. Patients who suffered from reflux oesophagitis with GERD-Q score ≥ 8 were 15 patients (65.2%) and GERD-Q score 8 were 2 patients (15.4%). Chi Square test analysis with confidence interval of 95% revealed p = 0.004 (p 0.05). Biserial point correlation coefficient was 0.643 with p 0.001.Conclusion: There was a strong relationship between GERD-Q score and reflux oesophagitis. The higher the GERD-Q score, the higher the possibility to suffer from reflux oesophagitis.